Bacillus cereus Bacteremia: An Unusual Case Following Food Poisoning. (28th October 2021) - Sabri, A; Cavalieri, S; Ahmad, F; Martin, S; Abushattal, A
Abstract: Introduction/Objective: Bacillus cereus is a spore-forming, gram-positive rod, well known for causing food poisoning. In addition, this bacterium often presents as a contaminant of blood cultures. Differentiating true bacteremia from contamination of blood samples is important as it has treatment implications. Early recognition is necessary, as it can cause septic shock if untreated. We present a challenging case of food poisoning with concomitant bacteremia in a young patient with a history of diabetes mellitus (DM), celiac disease, and new-onset chronic kidney disease (CKD). Methods/Case Report: A 23-year-old adult male with a history of DM, new-onset CKD, and celiac disease presented with nausea, intermittent vomiting, and lower abdominal pain for 2 weeks. On initial evaluation, he had normal blood pressure but tachypnea and tachycardia. Physical examination was significant for left lower quadrant and flank tenderness. The symptoms were persistent and progressed to point that he could not tolerate meals due to vomiting. Two weeks earlier, he presented with similar complaints along with dysuria and was treated for suspected urinary tract infection with Co-trimoxazole. This time, further workup revealed normal white blood cell count (11.8 k/µL) with 81% neutrophils, elevated creatinine (3.56 mg/dL), blood urea nitrogen (49 mg/dL), and procalcitonin (0.39 ng/mL), with abnormal urinalysis showing increased turbidity, pyuria, and nitrituria. He was started on ceftriaxone, fluids, antiemetics and was admitted to the hospital for further management. The urine culture had no bacterial growth. Two sets of peripheral blood cultures (different sites at different times) had gram-positive rods which eventually turned out to be B. cereus, identified by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). Levofloxacin was started, and he reported improvement in nausea and vomiting by the next day of admission and was discharged. Results (if a Case Study enter NA): NA Conclusion: Differentiating true B. cereus bacteremia from blood sample contamination is important. Additionally, no symptoms are specific for B. cereus-associated food poisoning, and the presence of risk factors doesn't always favor this entity over other entities, hence adding difficulty to the diagnosis. A high index of suspicion is needed, as early intervention can prevent the development of life-threatening complications.